The Correlation Between Teachers’ Teaching Style and Students’ Learning Engagement at MA Plus Nurul Islam Sekarbela - Fahmi, Rizkia Rahayu Aji; Nawawi, Nawawi; Wardana, Lalu Ali (Jurnal Ilmiah Profesi Pendidikan, 2025)
Student learning engagement is a multidimensional construct encompassing behavioral, emotional, and cognitive aspects, serving as a cornerstone for academic success. This study investigated the correlation between teachers’ teaching styles and student learning engagement at MA Plus Nurul Islam Sekarbela, addressing a research gap within the unique cultural and institutional environment of Indonesian Islamic schools. Utilizing a quantitative approach with a correlational research design, data were collected from 49 students in grades XI and XII using a structured self-report questionnaire adapted from Grasha’s teaching style model. Descriptive analysis revealed that overall perceived teaching styles were categorized as "High," with the student-centered Facilitator Style dominating Class XI Agama (Mean = 3.38) and the teacher-centered Expert Style dominating Class XII-B Agama (Mean = 3.30). Inferential statistics using Spearman's rho indicated no statistically significant linear correlation between overall perceived teaching style and student learning engagement (p > 0.05) in either grade. The findings suggest that institutional norms and cultural discipline may be stronger predictors of engagement than pedagogical style alone. It is concluded that educators should prioritize strategies targeting the emotional and cognitive dimensions of engagement to improve instructional quality.